2012
DOI: 10.1097/sih.0b013e31823d018a
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Simulation-Based Assessments With Other Performance Measures of Third-Year Anesthesiology Residents

Abstract: The associations between simulator performance, both for technical and nontechnical skills, and other markers of ability provide some evidence to support the validity of simulation-based assessment scores. Replication studies with larger numbers of residents are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Most of these studies showed positive results regarding the reliability and validity of simulation-based assessment when compared to traditional assessment methods. [333435] On the other hand, few studies showed some variability in reliability, especially on evaluating the behavioral aspects. The validity of simulation-based assessments to differentiate a large group of trainees based on clinical experience or training was confirmed in a previous study.…”
Section: Simulation-based Assessmentmentioning
confidence: 99%
“…Most of these studies showed positive results regarding the reliability and validity of simulation-based assessment when compared to traditional assessment methods. [333435] On the other hand, few studies showed some variability in reliability, especially on evaluating the behavioral aspects. The validity of simulation-based assessments to differentiate a large group of trainees based on clinical experience or training was confirmed in a previous study.…”
Section: Simulation-based Assessmentmentioning
confidence: 99%
“…At the end of a nursing program, the students' performance should reflect the expected competencies of new graduates. Simulations for summative assessment can be short, approximately 3 to 5 minutes, such as when assessing procedures and technical skills, or long, approximately 30 minutes, when assessing behaviors and nontechnical skills such as communication and teamwork (Mudumbai, Gaba, Boulet, Howard, & Davies, 2012). Longer scenarios allow the faculty to create a clinical situation that is complex enough to evaluate students' higher level skills, such as managing a changing patient's condition and setting priorities.…”
Section: Designing Appropriate Simulationsmentioning
confidence: 99%
“…[6] The American Board of Anesthesiology (ABA) has mandated simulated-based training as a part of the practice performance improvement and assessment component for the maintenance of certification in anesthesiology (MOCA). [22] The Accreditation Council for Graduate Medical Education (ACGME) proposed that specific outcomes should assess competency and improve education and performance feedback. [4] 2.…”
Section: Review Of the Literaturementioning
confidence: 99%